The importance of improving the legal regulation of animal treatment in terms of preventing cruelty - V. S. Seliukov (Bulletin of Kharkiv National University of Internal Affairs)
The subject of this article is a set of legal acts in Ukraine that regulate the general procedure and principles of animal treatment and the forms/methods of ensuring their welfare in the modern world. For a long time, the issues of protection and maintenance of normal conditions for the existence of the animal world have been somewhere “alongside” the need to regulate social relations, although everyone knows that the model of animal treatment is a prototype of a human behavioural algorithm in society.